God and Canada negotiations of selfhood and a sense of home and hope - Guieb, Eulalio R. (Philippine humanities review = Rebyu ng Arte at Literatura ng Pilipinas.)
"... describes how Filipinos in Montreal construct their sense of home, identity, and selfhood amidst global changes. Using Clifford Geertz's approach to culture, and writing his observations and insights in a manner similar to that of creative nonfiction, Guieb allows the reader an intimate view of the complex network of relations that inform the production of identity of Filipinos far away from their homeland." -- Introduction